THE INFLUENCE OF OPERATIONAL CASH FLOW, LEVELS OF DEBT, AND FIRM SIZE ON EARNINGS PERSISTENCE (EMPIRICAL STUDY OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE, 2019-2021) - Damayanty, Prisila; Astuti, Dyah Puji (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to examine the effect of Operational Cash Flow, Debt Level and Firm Size on Earnings Persistence. The population used in this research is all Property and Real Estate Companies on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample in this study was 36 units using purposive sampling method. Testing the hypothesis in this study using multiple linear regression analysis using SPSS version 26. The results of this study indicate that Operational Cash Flow and Firm Size have a significant positive effect on earnings persistence, while the level of debt has no significant effect on earnings persistence and. Operational Cash Flow, Debt Level and Firm S simultaneously have a significant effect on earnings persistence. Keywords: Earning Persistence, Operating Cash Flow, Debt Level and Firm Size